The influence of ENSO on South American precipitation during austral summer and autumn in observations and models. (19th May 2015) - Tedeschi, Renata G.; Collins, Matthew
ABSTRACT: South American precipitation is observed to respond differently to different types of El Niño Southern Oscillation (ENSO) events, such as those in which the main signal in sea surface temperature (SST) occurs either in the eastern equatorial Pacific or central equatorial Pacific. This study investigates how Coupled Model Intercomparison Project Phase 5 (CMIP5) models represent different types of ENSO and how they represent teleconnections to South American precipitation. It is found that the CMIP5 models can represent the basic structure of SST anomalies that occur during different types of ENSO events and these are described using simple SST indices. Most of the CMIP5 models can reproduce the correct sign of precipitation anomalies in northeast South America during austral summer and autumn, in cases where the observed teleconnections are relatively strong. The same is also true of north South America in austral summer. In the east and southeast regions of South America, many models fail to reproduce the correct sign during both Canonical and Modoki/Central Pacific/Warm Pool ENSO events. The precipitation composites in Atmospheric Model Intercomparison Project (AMIP) models tend to agree with their CMIP5 counterparts, so we conclude that the errors in teleconnections are not principally driven by mean SST biases. Precipitation teleconnections in the northern regions are shown to be linked to variations in the Walker circulation in models, with the exception of that in north South America during March–May. During March–May, composite precipitation in southeast South America is related to wave trains emanating from the equator.